2004
DOI: 10.1161/01.str.0000114202.86942.61
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Alcohol Dehydrogenase γ1/γ2 Gene Polymorphism and Risk of Stroke

Abstract: Background and Purpose-Genetic polymorphism of the alcohol dehydrogenase type 3 gene (ADH1C) has recently been associated with reduced risk of myocardial infarction. However, data on risk of stroke are not available. Methods-We examined the possible association between the ADH1C ␥1/␥2 polymorphism and risk of stroke in a prospective, nested case-control sample from the Physicians' Health Study of 14 916 apparently healthy men who were followed over a 12-year period. A total of 320 incident stroke cases and 550… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Yet, previous studies analyzing this issue were rather inconsistent showing the strongest inverse association between ADH1C*2/2 genotype and risk of coronary events either in men with the highest alcohol consumption of at least one drink/d [8], [9], or in men with a modest consumption of 1–3 alcoholic beverages/week [12]. Other studies provided little evidence for an association between ADH1C genotype and coronary events [10], [11] or stroke [13] across strata of alcohol consumption and the same applies to the association between ADH1B genotype and acute coronary syndrome [11]. In our study, there was no clear evidence that the slow-metabolizing ADH1C*2/2 genotype decreases risk of CVD in any stratum of alcohol consumption (Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, previous studies analyzing this issue were rather inconsistent showing the strongest inverse association between ADH1C*2/2 genotype and risk of coronary events either in men with the highest alcohol consumption of at least one drink/d [8], [9], or in men with a modest consumption of 1–3 alcoholic beverages/week [12]. Other studies provided little evidence for an association between ADH1C genotype and coronary events [10], [11] or stroke [13] across strata of alcohol consumption and the same applies to the association between ADH1B genotype and acute coronary syndrome [11]. In our study, there was no clear evidence that the slow-metabolizing ADH1C*2/2 genotype decreases risk of CVD in any stratum of alcohol consumption (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 36 references were excluded for the following reasons: no original data (n = 15), no relevant outcome (n = 16), no relevant exposure (n = 3), no relevant study design (n = 2). Thus, eight studies met our inclusion criteria of which one was examining stroke [13]. Eligible studies on ischemic heart disease included studies on CHD [7], [8], [12], MI [9], [10], and acute coronary events [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional study first examined brain magnetic resonance imaging in 376 men and women and found that men without the ALDH2 * 504Lys variant are more likely to have multiple lacunar infarcts [ 20 ]. No studies have reported the association between ALDH2 polymorphisms and stroke, whereas some studies have investigated the association between ADH polymorphisms and stroke [ 21 , 22 ]. In our study, analysis stratified by sex showed that the risk of stroke was significantly associated with the wild-type ALDH2 polymorphism in men, but not in women.…”
Section: Discussionmentioning
confidence: 99%